2013
DOI: 10.1016/s2255-4823(13)70463-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of chronic critical illness in a general intensive care unit

Abstract: To assess the incidence, costs, and mortality associated with chronic critical illness (CCI), and to identify clinical predictors of CCI in a general intensive care unit.Methods: This was a prospective observational cohort study. All patients receiving supportive treatment for over 20 days were considered chronically critically ill and eligible for the study.After applying the exclusion criteria, 453 patients were analyzed.Results: There was an 11% incidence of CCI. Total length of hospital stay, costs, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 27 publications
0
15
0
3
Order By: Relevance
“…1 A 32-bed intensive care unit (ICU) in southern Brazil reported that 42 of 453 (9.3%) patients received PMV in half a year. 2 While PMV incidence was 6.3 per 100 ventilated ICU admissions from 2002 to 2006 in the United Kingdom, 3 in Taiwan, the PMV rate fell from 94.3 to 89.38 per 100,000 persons from 2004 to 2007. 4 In the United States, a population-based study found that the incidence of tracheostomy for PMV was 24.2 per 100,000 people in 2002, and this rate had increased by nearly 200% from the previous decade.…”
Section: Introductionmentioning
confidence: 99%
“…1 A 32-bed intensive care unit (ICU) in southern Brazil reported that 42 of 453 (9.3%) patients received PMV in half a year. 2 While PMV incidence was 6.3 per 100 ventilated ICU admissions from 2002 to 2006 in the United Kingdom, 3 in Taiwan, the PMV rate fell from 94.3 to 89.38 per 100,000 persons from 2004 to 2007. 4 In the United States, a population-based study found that the incidence of tracheostomy for PMV was 24.2 per 100,000 people in 2002, and this rate had increased by nearly 200% from the previous decade.…”
Section: Introductionmentioning
confidence: 99%
“…Admission of patients for nonsurgical reasons has been previously identified as a factor associated with the evolution to chronic critical illness [3,23]. The severity scores have been considered predictors of prolonged MV [3,17,23,29]. Our data, at admission, are not consistent with this assumption.…”
Section: Discussionmentioning
confidence: 56%
“…Previous authors have found higher mortality in PMV patients [7,17,20,22,23], while others have not [6,22]. The reason for these discrepancies is probably related to the heterogeneity and intrinsic characteristics of studies' populations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…13,14 Inadvertent undernutrition and unnecessary fasting is associated with a greater chance of chronic critical illness. 15 Monitoring metabolic aspects in conjunction with the clinical context of these patients increase the likelihood of successful outcomes. This team ideally includes a medical specialist, a nutritionist, a nurse, and a pharmacist.…”
Section: Lustmentioning
confidence: 99%